Genome‐wide dissection of hybridization for fiber quality‐ and yield‐related traits in upland cotton. (11th November 2020) - Geng, Xiaoli; Sun, Gaofei; Qu, Yujie; Sarfraz, Zareen; Jia, Yinhua; He, Shoupu; Pan, Zhaoe; Sun, Junling; Iqbal, Muhammad S.; Wang, Qinglian; Qin, Hongde; Liu, Jinhai; et al.
SUMMARY: An evaluation of combining ability can facilitate the selection of suitable parents and superior F1 hybrids for hybrid cotton breeding, although the molecular genetic basis of combining ability has not been fully characterized. In the present study, 282 female parents were crossed with four male parents in accordance with the North Carolina II mating scheme to generate 1128 hybrids. The parental lines were genotyped based on restriction site‐associated DNA sequencing and 306 814 filtered single nucleotide polymorphisms were used for genome‐wide association analysis involving the phenotypes, general combining ability (GCA) values, and specific combining ability values of eight fiber quality‐ and yield‐related traits. The main results were: (i) all parents could be clustered into five subgroups based on population structure analyses and the GCA performance of the female parents had significant differences between subgroups; (ii) 20 accessions with a top 5% GCA value for more than one trait were identified as elite parents for hybrid cotton breeding; (iii) 120 significant single nucleotide polymorphisms, clustered into 66 quantitative trait loci, such as the previously reported Gh_A07G1769 and GhHOX3 genes, were found to be significantly associated with GCA; and (iv) identified quantitative trait loci for GCA had a cumulative effect on GCA of the accessions. Overall, our results suggest that pyramiding the favorable loci for GCA may improve the efficiency of hybrid cotton breeding. Significance Statement: General and specific combining ability values are very important factors for the selection of appropriate parents and superior combinations in hybrid cotton breeding, although the molecular genetic basis has not been fully characterized. In the present study, we identified significant single nucleotide polymorphisms for general and specific combining ability in a large‐scale North Carolina II population through a genome‐wide association study. The results obtained provide new insights with respect to our understanding of the genetic factors related to combining ability.